Retroperitoneoscopic Ablative Renal Surgery in Children:The Feasibility of Using Three Trocars - Oktar, Tayfun; Sanli, Oner; Acar, Omer; Tefik, Tzevat; Karakus, Serkan; Ziylan, Orhan (Urology Journal, 2014)
Purpose: We report the results of pediatric retroperitoneoscopic renal ablative surgeries, which were performed with only three trocars. Materials and Methods: We retrospectively reviewed the charts of children who underwent laparoscopic urological procedures on the upper urinary tract at our institution between 2006 and 2012. These procedures consisted of nephrectomies, nephroureterectomies and heminephroureterectomies. The operations were performed retroperitoneoscopically with three trocars. The specimens were removed intact through the primary trocar site. Results: A total of 30 retroperitoneoscopic ablative surgeries were performed in 13 girls and 17 boys. The mean patient age was 7.8 ± 4.3 years (range, 1-14 years). The interventions consisted of nephrectomy in 10 cases (33.3%), nephroureterectomy in 17 cases (56.6%) and heminephroureterectomy in 3 (10%) cases. The open conversion rate was 3.3% (1/30). The difference between the initial 10 cases and the latter 20 cases, in terms of mean operative time, was statistically significant (144.5 vs. 115.78 minutes, respectively, P = .031). Apart from 3 nephroureterectomies, all of the procedures (86.6%) were completed successfully using three trocars only, without the need for a separate extraction incision. The patients were hospitalized for a mean duration of 2.2 days (range, 2-4 days). None of the patients required blood transfusion. We did not encounter any major perioperative or postoperative complication. Conclusion: Retroperitoneoscopic renal ablative surgery is a safe and effective treatment alternative for a variety of upper urinary tract disorders in children.